1.56. Rozwiąż równania: – (1/3) ^ (2x) – 12 * (1/3) ^ x + 27 = 0 (1/5) ^ (2x) – 24 * 5 ^ (- x) – (1/5) ^ – 2 = 0 a) b) 3^ |x+1|+1 -5*3^ x+1|-1 =12 2 ^ (2 + (x – 3)/x) – 5 * (1/2) ^ ((3 – x)/x + 2) = 11 d) b) 7 ^ (2x) + 4 * 7 ^ x – 5 = 0 d) 2 ^ (2x) + 5 * 2 ^ x + 6 = 0

1.56. Rozwiąż równania: – (1/3) ^ (2x) – 12 * (1/3) ^ x + 27 = 0 (1/5) ^ (2x) – 24 * 5 ^ (- x) – (1/5) ^ – 2 = 0 a) b) 3^ |x+1|+1 -5*3^ x+1|-1 =12 2 ^ (2 + (x – 3)/x) – 5 * (1/2) ^ ((3 – x)/x + 2) = 11 d) b) 7 ^ (2x) + 4 * 7 ^ x – 5 = 0 d) 2 ^ (2x) + 5 * 2 ^ x + 6 = 0

Kliknij aby dołączyć do Akademii Matematyki

Dodaj komentarz